A mitochondrial therapeutic reverses visual decline in mouse models of diabetes - Nazia M. Alam; William C. Mills; Aimee A. Wong; Robert M. Douglas; Hazel H. Szeto; Glen T. Prusky (The Company of Biologists, 2015)
Diabetic retinopathy is characterized by progressive vision loss and the advancement of retinal micoraneurysms, edema and angiogenesis. Unfortunately, managing glycemia or targeting vascular complications with anti-vascular endothelial growth factor agents has shown only limited efficacy in treating the deterioration of vision in diabetic retinopathy. In light of growing evidence that mitochondrial dysfunction is an independent pathophysiology of diabetes and diabetic retinopathy, we investigated whether selectively targeting and improving mitochondrial dysfunction is a viable treatment for visual decline in diabetes. Measures of spatial visual behavior, blood glucose, bodyweight and optical clarity were made in mouse models of diabetes. Treatment groups were administered MTP-131, a water-soluble tetrapeptide that selectively targets mitochondrial cardiolipin and promotes efficient electron transfer, either systemically or in eye drops. Progressive visual decline emerged in untreated animals before the overt symptoms of metabolic and ophthalmic abnormalities were manifest, but with time, visual dysfunction was accompanied by compromised glucose clearance, and elevated blood glucose and bodyweight. MTP-131 treatment reversed the visual decline without improving glycemic control or reducing bodyweight. These data provide evidence that visuomotor decline is an early complication of diabetes. They also indicate that selectively treating mitochondrial dysfunction with MTP-131 has the potential to remediate the visual dysfunction and to complement existing treatments for diabetic retinopathy.